A study on EMBA students' cognitive and decision-making models in learning through play. Issue 1 (March 2023) - Jhan, Ya-Cing; Luarn, Pin; Lin, Hong-Wen
Abstract: In light of rapid changes in global sectors, the cultivation of middle-senior managers have become more important than ever. And as such, numerous incumbent middle-senior managers across different companies have chosen to complete their Executive Master of Business Administration (EMBA) while still working full-time at their jobs. Needless to say, EMBA students' profound experience in decision-making at their relevant career domains serves as an invaluable source of data for related researches. Therefore, by investigating and analyzing the cognitive and decision-making models of EMBA students, we can potentially formulate innovative teaching strategies that can cultivate more management talents. In this study, lag sequential analysis has been chosen to process the cognitive and decision-making models of EMBA students as they learn through play. The differences in cognitive and decision-making models of students in different performance groups have also been analyzed. The study found that the cognitive and decision-making models of EMBA students are highly interactive in nature. Not only that, the cognitive and decision-making models of students in different performance groups reveal significant differences. By comparing students in the two groups, the study would recommend business schools and enterprises adopt learning through playing or establish systems of adaptive game-based learning for students. Highlights: Lag sequential analysis has been chosen to process the cognitive and decision-making models of EMBA students as they learn through play. The cognitive and decision-making models of EMBA students are highly interactive in nature. The cognitive and decision-making models of students in different performance groups reveal significant differences.